Asuransi Bank Syariah Indonesia - Mario Valentino; Sabrina Aisyah Putri; Mad Sohib (Pusat Riset dan Inovasi Nasional, 2024)
According to Islamic law, sharia insurance refers to mutual help. In general, sharia insurance, also known as at'ta'min, takaful, and tazamun, is an effort between a number of people or parties to protect and help each other through investment in the form of tabarru assets and/or funds. which offers a pattern of return for managing certain risks through Shariah-compliant contracts. To obtain information about risk management in sharia insurance, this study uses a type of literature research, collecting secondary data from books, magazines, the internet, and supporting data sources. The findings of this study are risk management to solve the inevitable problems in sharia insurance. Risk is the uncertainty of future events and outcomes. According to the type of risk that exists in a particular scenario, risk is described as something that, based on internal and external variables, can make it difficult for the company to achieve its goals. Must comply with OJK rules when planning risk management for sharia insurance.